A new gall midge of the genus Dentifibula (Diptera: Cecidomyiidae), a predator of the scale insect Aulacaspis australis feeding on mangrove Bruguiera gymnorrhiza. Issue 1 (13th September 2013) - Kolesik, Peter; De Faveri, Stefano
Abstract Dentifibula nigroapicalis Kolesik sp. nov., a new species of gall midge, is described whose larvae were found preying on the mangrove scale insect Aulacaspis australis Brimblecombe (Hemiptera: Coccoidea: Diaspididae). The mangrove scale was feeding on leaves of the mangrove Bruguiera gymnorrhiza (Rhizophoraceae) in Queensland. The new species is the first Dentifibula Felt known from Australia.